Effect of phosphorus application on the productivity and quality of three Stylosanthes cultivars - Mohamed-Saleem, M.A.; Kaufmann, Ralph R. von (1986)
In the subhumid zone of Nigeria S. guianensis cv Cook, S. Guianensis cv Schofield and S. hamata cv Verano produced low dry matter yields. The role of P in limiting yields was investigated in a field experiment at Kurmin Biri, Kaduna State, Nigeria. Four levels of P2O5, zero, 40, 80 and 120 kg ha-1, were applied to these stylos in 1981 and the experiment was run for two years, without further P additions, in order to determine residual levels. S. guianensis cv CooK responded most to increasing levels of P up to 80 kg P2O5 ha-1; the same trend was shown by cv Schofield but the response was less marked. S. hamata cv Verano did not respond in DM yield but the application of P gave improved seed production and increased P content in the tissue. P levels marginally increased the digestibility of the forage produced. Nodulation was not affected by P application for cv Verano but there was a marked effect in cvs Cook and Schofield. Crude protein was increased by P applications. In the second year, when no additonal P was applied, productivity of cvs Cood and Schofield declined by 60-70% but cv Verano remained only slightly affected. P application and legume growth increased organic C and N which suggest possibilities for enhancing integrated crop-livestock systems.